ANALISIS PERKEMBANGAN GIRO, TABUNGAN DAN DEPOSITO TERHADAP PERKEMBANGAN KREDIT PADA PT. BANK RAKYAT INDONESIA (PERSERO) CABANG PEMBANTU LATIMOJONG MAKASSAR - Andi Widiawati (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2015)
The following research aims to analyze the influence of third party funds, such as: demand deposit, saving deposit and time deposits to the development of credit amount at PT. Bank Rakyat Indonesia (Persero) Branch Office Latimojong Makassar. And this research was conducted over two (2) months. This research uses descriptive analysis method and analytical test reggression method. The results that obtained through simultaneous analysis, demand deposit, saving deposits and time deposit significantly influence the development of the credit amount. Similarly, the results obtained through the analysis of the partial test of the three variables such as current accounts, demand deposit, saving deposit and time deposit shows a positive and significant influence on the development of credit amount at PT. Bank Rakyat Indonesia Branch Office Latimojong Makassar.